Clinical relevance of PLK1 in epithelial ovarian cancer - Shen, Xiaochang; Wang, Jiandong; Chen, Shuning; Zhang, Haomeng; Zhou, Chunxiao; Bae-Jump, Victoria L. (Frontiers in Pharmacology, 2025)
Ovarian cancer, particularly epithelial ovarian cancer (EOC), is the most aggressive and lethal gynecologic malignancy, necessitating the development of innovative and potent therapies to improve its prognosis. Human polo-like kinase 1 (PLK1), a key regulator of cell division, is crucial for driving mitosis and cytokinesis and maintaining genomic stability through phosphorylation of a few different substrates. PLK1 is found to be overexpressed in EOC tissues compared with normal ovarian tissues and is strongly associated with the prognosis of patients with stage I and II EOC. Targeting PLK1 markedly inhibits cell proliferation, causes cell cycle G2 phase arrest and DNA damage, induces apoptosis, and reduces tumor growth in preclinical models of EOC. In addition, the combination of PLK1 inhibitors with chemotherapeutic agents such as paclitaxel, cisplatin, doxorubicin, and PARP inhibitors exhibits effective synergistic effects in cell proliferation and tumor growth in EOC. Phase I and II clinical trials of PLK1 inhibitors in patients with EOC have shown favorable safety but inconsistent clinical efficacy. This review analyzes the existing preclinical and clinical data on PLK1 and evaluates the antitumor effects of PLK1 in EOC, offering perspectives on the potential application of PLK1 in the treatment of EOC.